Strengthening Tourism Products Through Storytelling Exploration in Kemiriombo, Gerbosari Village, Samigaluh District, Kulonprogo Regency - Iban, Carlos; Marsono; Fatkurrohman; Nuryani, Anik; Rahayuningsih, Handayani; Bayu Aji, Khusnul (Universitas Terbuka, 2024)
Kemiriombo, a hamlet in Gerbosari Village, Kulon Progo, Yogyakarta, is known for its diversity of spices (empon-empon) cultivated and processed by the local community. This area has significant potential for developing tourism based on local culture and traditions, but the tourism narrative has not been optimally managed. This study aims to explore the potential of storytelling as a strategy for developing tourist destinations in Kemiriombo. The methods used include observation, interviews, Focus Group Discussions (FGD), surveys, and community participation to understand the needs and expectations of the local community. The study found that Kemiriombo has tourism potential such as the processing of empon-empon at Rumah Jamu Menoreh, local cultural arts such as Jathilan, Gejog Lesung, and Karawitan, as well as culinary traditions like Sega Brongsong and Legondo. The 5W1H technique (Who, What, When, Where, Why, How) was applied in the storytelling analysis to produce engaging narratives that can promote local cultural identity. Storytelling plays a crucial role in introducing local products and traditions, enhancing tourist attraction, and preserving community culture. Through the development of strong narratives, Kemiriombo is expected to become a tourist destination that offers not only visual experiences but also emotional and social dimensions for visitors. The integration of local traditions and storytelling innovation is expected to positively impact the welfare of the local community.